FORMULATION OF HONEY AND DATES FOR NUTRITIONAL SUPPORT IN PREGNANT WOMEN 2024 - Elfridayani; Sihite, Esima ondela; Sari, Mayang; Batubara, Zulkarnain; Yuniarti, Winda; Rosmega; Syafrida (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background :Anemia in pregnancy remains one of the major contributors to the high Maternal Mortality Rate (AKI) in Indonesia requiring proper management, one of which is through nutritional approach alternatives with dates and honey rich in iron, vitamin C, and other nutrients supporting red blood cell formation. Objectives : This study aims to explore and determine the significant effect of providing dates and honey on the increase of hemoglobin levels in pregnant women in the third trimester in the working area of Gunungtua Health Center, Mandailing Natal in 2024. Methods : The research method implemented is a quantitative approach with a quasi-experimental design of pretest-posttest with control group. Sampling technique used is total sampling involving a total population of 32 pregnant respondents meeting inclusion criteria, then evenly divided into 16 respondents for the intervention group (given treatment) and 16 respondents for the control group (not given treatment). Results : Based on observations before intervention (pre-test), all respondents (100%) in the intervention group and 66.7% of respondents in the control group were identified as having anemia. However, after intervention with dates and honey (post-test), there was a very significant improvement where 100% of pregnant women in the intervention group were free from anemia, while the control group still had 53.3% with anemia. Hypothesis testing through bivariable statistical analysis using Chi-Square test yielded a p-value of 0.002 (p < 0.05), which statistically confirms a positive and significant effect of consuming dates and honey on the occurrence of anemia. Also supported by a Relative Risk (RR) value of 3.14 indicating that pregnant women who do not consume dates and honey are 3.14 times more likely to remain anemic than those who regularly consume them. Conclusions : In conclusion, the intervention of giving dates and honey proved effective to be applied as a nutritional supplement for pregnant women to naturally raise hemoglobin levels and reduce complications due to iron deficiency anemia in the community.